PENGARUH EFIKASI DIRI, LINGKUNGAN SOSIAL, AKSES KEPADA MODAL, DAN KEPEMILIKAN JARINGAN SOSIAL TERHADAP SIKAP KEWIRAUSAHAAN MAHASISWA PROGRAM STUDI PENDIDIKAN AKUNTANSI ANGKATAN 2013 UNIVERSITAS NEGERI SEMARANG - Lestari, Retno Ariyani Puji; Yulianto, Agung (Universitas Negeri Semarang, 2017)
This study aims to find out the influence of self efficacy, social environment, access to capital, and ownership of social networks on student entrepreneurship attitude of Accounting Education Program year 2013 UNNES either simultaneously or partially. The population in this study were students of Accounting Education class of 2013 amounting to 190 students and 129 students sample after treatment with the standard formula Slovin error of 5% then using Random Propotional Sampling as the sampling technique. This study used a questionnaire as a data collection tool. Data were analyzed using descriptive statistical analysis and regression analysis. The results showed that self-efficacy, social environment, access to capital, and the ownership of social network influence simultaneously to accounting education student entrepreneurship attitude (70%). Partially self efficacy affected student entrepreneurship attitude (44,09%), social environment does not affected students entrepreneurship attitude (0,19%), access to capital does not affected student entrepreneurship attitude (0,05%), and ownership of social networks affected student entrepreneurship attitude (13,76%).